Implementasi Sistem Marketplace “Pasar Kita” Berbasis Web Menggunakan PHP dan MySQL - Dwi Utami; Nurhidayah Nurhidayah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study focuses on the development and implementation of “Pasar Kita,” a web-based marketplace system designed to facilitate digital transactions for traditional market sellers and consumers. The system was developed using PHP as the backend programming language and MySQL as the database management system. The purpose of this project is to address the digital gap experienced by traditional market vendors who have limited access to modern e-commerce platforms. The research includes a needs analysis, system design using UML diagrams, implementation of main features such as registration, login, product management, transactions, checkout, and order tracking, followed by system testing. The results show that all major functions operate properly, including user authentication, product uploads, order processing, and payment simulations via transfer or cash-on-delivery (COD). System testing indicates that the platform meets usability, functional, and responsiveness criteria. The findings highlight the system’s capability to support local economic digitalization by providing an accessible and user-friendly marketplace for traditional market vendors and consumers.